Surgical management practice of pelvic organ prolapse among Ethiopian gynecologists, 2021: a descriptive study - Zelalem Ayichew Workineh; Birhanu Abera Ayana; Kiros Terefe Gashaye; Solomon Berhe Wubneh; Belayneh Ayanaw Kassie (BMC, 2023)
Abstract Introduction Pelvic Organ Prolapse is the descent of one or more of the anterior vaginal wall, posterior vaginal wall, the uterus, or the apex of the vagina. Surgical intervention addresses both anatomical defect and associated symptoms. The landscape of prolapse surgery has been evolving constantly over years. Emerging evidences either support or challenge existing surgical treatment options, making urogynecology a dynamic field. In Ethiopia, the surgical management of pelvic organ prolapse has transitioned from abdominal to vaginal hysterectomy, supplemented later by McCall's culdoplasty. Disparities exist in the national uniformity of surgical approaches, linked to the establishment of Urogynecology centers in certain institutions. Objectives This study was done to assess the surgical management practice of Ethiopian gynecologists on pelvic organ prolapse. Methods A cross-sectional study encompassing all Gynecologists in Ethiopia took place between January to June 2021. Information was gathered through online Google forms crafted in English. Subsequently, the collected data underwent verification, coding, and entry into Epi info 7 before being exported to SPSS version 22 software for descriptive statistical analysis. Results We reached 280 gynecologists out of the 450 practicing in the Ethiopia making 62% response rate. Anterior colporrhaphy (98.6%), vaginal hysterectomy with McCall's cul-do-plasty (51.8%), and Posterior colporrhaphy (97.5%) were the most commonly performed surgical procedures for anterior vaginal wall prolapse, apical prolapse (uterine/cervical), and posterior vaginal wall prolapse respectively. Only 3.2% and 0.7% of the gynecologists conducted abdominal and vaginal paravaginal repair for anterior vaginal wall prolapse. Sacrospinous ligament fixation and sacrocolpopexy for apical prolapse were carried out by 32.9% and 9.3% of the gynecologists respectively. Site-specific posterior repair for posterior vaginal wall prolapse was performed only by 23.9% of the gynecologists. The main reasons mentioned not to perform paravaginal repair, sacrocolpopexy, sacrospinous ligament fixation, and site-specific posterior repair were lack of skill and lack of appropriate materials. Conclusion and recommendation Most gynecologists in Ethiopian continue to perform vaginal hysterectomy and colporrhaphy procedures for treatment of pelvic organ prolapse due primarily to lack of skill and appropriate materials to perform the alternative procedures. Implementing short term training on alternative surgical treatment options of pelvic organ prolapse with provision of suitable materials and increasing the number of urogynecologists in the country in the long run holds the potential to enhance the standard of care of women with the condition.